Clinicopathological Features of Colorectal Cancer in the Iraqi Population Focusing on Age and Early-Onset of Malignancy: A Descriptive Cross-Sectional Study - Farhad, Rand Mutanna; Saleh, Eman Saadi; Alsammarraie, Ahmed Zuhair (Al-Rafidain Journal of Medical Sciences ( ISSN 2789-3219 ), 2023)
Background: Colorectal cancer (CRC) is one of the top ten most common cancers worldwide. There are multiple risk factors for CRC, one of which is aging. However, in recent years, CRC has been reported in children. Objective: To describe the main characteristics and symptoms of CRC as well as highlight pathologic data for early-onset CRC. Methods: 79 CRC patients were recruited from the Oncology Teaching Hospital in the period February–December 2022. A questionnaire was used to collect demographic and clinical data. Results: 25 (31.6%) of patients were below 50 years of age. 52 (65.8%) patients had tumors in the colon. The most common symptom is bleeding per rectum in both age groups. There was no significant difference in pathologic characteristics between early- and late-onset CRC. Conclusion: Although older people are more likely to develop CRC, both age groups can be affected. Younger and older individuals both had roughly similar symptoms and clinicopathologic features.